M-CBIR: A Medical Content-Based Image Retrieval System Using Metric Data-Structures - López Del Alamo, Cristian (2013)
This work is focused on the modeling and development of a CBIR (Content-based image retrieval) system applied to the recovery of digital medical images of a human body, denominated M-CBIR. This model is composed on two methodologies: features extraction techniques and metric data structures. When this set of techniques is applied to the search of different human body regions, it can retrieve the most relevant similar images to a query image. A real database of medical images composed of 772 medical studies was used to compare the robustness of the extraction techniques and evaluate the performance of the system, through four different extractors. The objective of this work will result in a digital atlas of human body for medical radiological center. Finally, analysis and conclusions are also discussed.